Manifesto for Socially Engaged Clinical Practice in the Behavioral Sciences - Neves, Ana Barbara Vieira Sinay; Amorim, Virgínia Cordeiro; Borba, Aécio; Souza, Fabrício de; Silveira, Jocelaine Martins da; Passos, Jonatas Argemi Foster; Nicoldi, Laís; Cihon, Traci (Perspectivas em Análise do Comportamento, 2023)
In this manifesto we argue that it is the essential duty of every behavior analyst and contextual behavioral scientist to develop analyses and interventions that are committed to the material and socio-political-cultural reality in which their clients are inserted. We base this defense on the argument that considering individual behavior detached from the cultural context can lead to analyses that make certain oppressive practices invisible and that open space for the perpetuation of structural violence and clinical iatrogenesis. In this sense, we state that, despite the various initiatives on the national and international scene that understand the importance of studying cultural variables in the context in which therapist and client find themselves, there is still a gap in the systematization of the conceptualization of clinical cases, and in the operationalization of the inclusion of these cultural variables in the functional analysis of each case. Therefore, we propose here to initiate a broad collaboration to develop methodologies for analysis and interventions that incorporate and systematize behavioral and cultural aspects for a socially engaged clinical practice. Next, we list suggestions for general guidelines for research, professional training, and socially engaged clinical practice in the field of professional practice, scientific production, and training.